FE analysis of geometrically nonlinear static problems with follower loads - Kozák, Imre; Nándori, Frigges; Szabó, Tamás (Computer Assisted Methods in Engineering and Science, 2023)
We have considered a linearly elastic body loaded by tractions inward normal to the instantaneous surface. Due to the increment of the surface element vector there is a contribution to the tangent stiffness matrix referred to as load correction stiffness matrix. The goal of the numerical experiments is to determine the bifurcation point on the fundamental equilibrium path. Linear eigenvalue problems with follower loads are also analysed.